DIVERSIFIKASI PRODUK ANYAMAN PANDAN MELALUI PENDIDIKAN DAN LATIHAN KETERAMPILAN DI DESA CIMPUNGAN KECAMATAN SIBERUT TENGAH KABUPATEN KEPULAUAN MENTAWAI - YUSTINUS LEPAAKEN. S, Dra. Zubaidah,M.Sn, Drs. Abd. Hafiz, M.Pd (Serupa The Journal of Art Education, 2014)
The purposes of this study is to providing change and progress towards outcomes of woven of pandan products, and increase the motivation and creativity of the craftsmen. Researcher diversify the product through Training the skills. The primary data source is directly by informants through a questionnaire and Literature secondary data is the documentation. Type of research is a field study. Techniques processing data using tabulation data, to analyze the data by comparing the percentage scores obtained with the existing of test scores. The results of the Research provide that products have undergone changes and developments, the craftsmen are motivation and creativity have been increase. Contribution of this study raise the community's economy in the handicraft industry, especially in woven pandan mats in the village of Cimpungan Central District of Siberut. So it can be recommended relationship fostered cooperation between the departments of industry Mentawai Islands by craftsmen of Cimpungan.Keywords: Diversification, woven pandan, Motivation, Creativity, Cimpungan